2022
DOI: 10.1037/pro0000480
|View full text |Cite
|
Sign up to set email alerts
|

Psychologist attitudes toward DSM-5 and its alternatives.

Abstract: A survey of psychologists’ attitudes toward the Diagnostic and Statistical Manual of Mental Disorders–5 (DSM-5), and its alternatives was conducted. Almost 90% of psychologists reported regularly consulting DSM-5, despite dissatisfaction with it. However, opinions varied by theoretical orientation. Cognitive-behavioral psychologists held positive attitudes about DSM, whereas psychodynamic and humanistic/constructivist/systems psychologists were negatively inclined toward it. Integrative/eclectic psychologists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
0
6
0
3
Order By: Relevance
“…For example, Balling et al (2022) found that clinicians rated HiTOP as having better clinical utility than the DSM when applying both systems to a clinical vignette. Raskin et al (2022) also found support from psychologists for alternatives to the DSM-5 in principle, but in practice they were unfamiliar with HiTOP.…”
Section: Hitop For a Better Classification Of Mental Disordersmentioning
confidence: 97%
“…For example, Balling et al (2022) found that clinicians rated HiTOP as having better clinical utility than the DSM when applying both systems to a clinical vignette. Raskin et al (2022) also found support from psychologists for alternatives to the DSM-5 in principle, but in practice they were unfamiliar with HiTOP.…”
Section: Hitop For a Better Classification Of Mental Disordersmentioning
confidence: 97%
“…Insgesamt führen die hier genannten Kritikpunkte dazu, dass Forschungsergebnisse zu einzelnen Störungen schwer interpretierbar sind und Diagnosen für die individuelle Fallformulierung und Therapieplanung oft als nicht sonderlich nützlich wahrgenommen werden (Balling et al, 2023;Bornstein & Natoli, 2019;First et al, 2018;Raskin et al, 2022).…”
Section: Zusammenfassungunclassified
“…As competing theories regarding the origins and potential treatments of psychosis have become myriad (Bentall, 2004; Cooke, 2017), examples can be seen in clinical mental health practice of what Kuhn (1962, p. 69) describes as the ‘breakdown of normal technical puzzle solving activity’. The instruments that historically had been used to support the ‘normal science’ of working within the biological paradigm, such as the diagnostic and statistical manual (American Psychiatric Association, 2013) to classify mental illness, are perceived as having less value within contemporary healthcare (Raskin et al, 2022). Moreover, the tools that had previously been considered the foundation of practice, such as antipsychotic medications are treated with much greater ambivalence, and for some are no longer the primary focus of therapeutic work (Bressington & White, 2015; Morant et al, 2018; R. M. Murray et al, 2016; Odeyemi et al, 2018).…”
Section: The Contemporary Paradigmatic Crisismentioning
confidence: 99%